Best "New" African Poets 2018 Anthology - Mala, Nsah, 1988-; Mwanaka, Tendai R. (Book collections on Project MUSE., 2019)
Best "New" African Poets 2018 Anthology follows volumes in 2017, 2016 and 2015. In this fourth volume of these continent-wide anthologies of African poetry we have work from 154 African poets from over 30 African countries and the African Diasporas. There are poems in English, French, Portuguese, Sepedi, Shona, Yoruba, and Asante Twi languages. In 2018 there was a notable increase in the number of entries with memorable novelties regarding poetic experimentation: some of the poets have daringly sliced up words playing around with the spatial and structural patterns of their texts on paper. This may be described as both textual and visual poetry. Reading the poems becomes a journey with many paths, where the reader walks according to poetic rhythms and the hesitating breaks of action verbs and enjambments.